Comparative review of multi-phase apparent power definitions - Balci, Murat Erhan; Hakan Hocaoglu, M. Hakan (My University, 2009)
In this paper, the widely recognised apparent power definitions are rigorously reviewed and their ability on the measurement of the system efficiency is investigated by using the apparent power definition, which is calculated in terms of the total line loss of the system with compensation and without compensation. Therefore, in a test system, the results are obtained for minimum rms current compensation strategy by taking into account the unbalance among the resistances of neutral and phase lines. © 2010 Elsevier B.V., All rights reserved.
6th International Conference on Electrical and Electronics Engineering, ELECO 2009 -- Bursa -- 79288
Keywords: Apparent power; Current compensation; Line loss; System efficiency; Test systems; Electronics engineering